The influence of perceived stress of Chinese healthcare workers after the opening of COVID-19: the bidirectional mediation between mental health and job burnout - Jiang, Minhui; Li, Zhangjie; Zheng, Xiaomin; Liu, Min; Feng, Yaling (Frontiers in Public Health, 2023)
Objective: To explore the current status and interaction of perceived stress, job burnout and mental health among healthcare workers after the opening of COVID-19 which occurred in December 2022. Methods: A cross-sectional study of 792 healthcare workers from three tertiary hospitals in Wuxi was conducted from January 2023 to February 2023. Sociodemographic questionnaire, Perceived Stress Scale, Burnout Scale and Mental Health Self-Assessment Questionnaire were used for investigation. SPSS 26.0 was used to conduct data analysis. The significance of mediation was determined by the PROCESS macro using a bootstrap method. Results: The results showed that (1) The average scores of the participants for perceived stress, mental health and job burnout were 22.65 (7.67), 3.85 (4.21) and 1.88 (1.03), respectively. (2) The perceived stress score, mental health score and job burnout score of healthcare workers were positively correlated (r=0.543-0.699, P<0.05). (3) Mental health partially mediated the relationship between perceived stress and job burnout with a mediating effect of 17.17% of the total effect. Job burnout partially mediated the correlation between perceived stress and mental health with a mediating effect of 31.73% of the total effect. Conclusion: The results of this study suggested that perceived stress had an impact on job burnout and mental health, either directly or indirectly. Healthcare managers should intervene to reduce perceived stress to protect healthcare workers’ mental health, thereby alleviating burnout under the opening COVID-19 pandemic environment.